2022
DOI: 10.1111/apt.16910
|View full text |Cite
|
Sign up to set email alerts
|

Letter: non‐invasive transabdominal stimulation device for the treatment of chronic constipation—proof‐of‐principle study in adults. Authors’ reply

Abstract: Nearly half of patients with chronic constipation are dissatisfied with traditional treatment options. 1 Our review article on constipation disorders briefly mentioned sacral nerve stimulation(SNS). 2 We commend Talley et al on their efforts in expanding treatment options for constipation. 3 They describe their promising experience using a non-invasive TENS device in a proof-of-principle study by treating 20 patients with chronic constipation. They found significant improvements in symptoms and quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…3). A proof-of-concept study using a tailored TENS device demonstrated improvements in symptoms and quality of life, although completion rates were low and device tolerability might be an issue [32,33]. Transabdominal interferential electrical stimulation, a varied form of TENS therapy, also demonstrated improved bowel pattern compared with sham stimulation in women with refractory constipation [34].…”
Section: Nonpharmacological Treatmentsmentioning
confidence: 99%
“…3). A proof-of-concept study using a tailored TENS device demonstrated improvements in symptoms and quality of life, although completion rates were low and device tolerability might be an issue [32,33]. Transabdominal interferential electrical stimulation, a varied form of TENS therapy, also demonstrated improved bowel pattern compared with sham stimulation in women with refractory constipation [34].…”
Section: Nonpharmacological Treatmentsmentioning
confidence: 99%